Management of linseed powdery mildew through soil and foliar application of sulphur: MANAGEMENT OF LINSEED POWDERY MILDEW THROUGH APPLICATION OF SULPHUR - K AJITHKUMAR; S A BIRADAR; B RAJANNA; P K SINGH; I SHANKER GOUD (Journal of Oilseeds Research, 2017)
A field experiment was conducted during rabi 2013-14 and 2014-15 to test the efficacy of soil and foliar application of sulphur against powdery mildew in linseed. The pooled results showed that two sprays of wettable sulphur (0.4%) recorded minimum disease of 13.5 per cent with maximum yield (555 kg/ha) and BC ratio (2.68). It was followed by soil application of sulphur (30 kg/ha) through gypsum at the time of sowing followed by two sprays of 0.3 per cent wettable sulphur found promising and recorded less disease, seed yield and BC ratio of 18.5 per cent, 526 kg/ha and 2.44, respectively.